Critical thinking a user's manual - Jackson, Debra L.; Newberry, Paul (Cengage Learning, 2016)
"Critical thinking: a user's manual offers an innovative skill-based approach to critical thinking that provides step-by-step tools for learning to evaluate arguments. Students build a complete skill set by recognizing, analyzing, diagramming, and evaluating arguments. Later chapters encourage application of the basic skills to categorical, truth-functional, analogical and inductive, and causal arguments as well as fallacies. Clear, conversational, step-by-step explanations and workbook-style features make complex course material manageable and accessible. Multiple opportunities for practice in a variety of formats ensure that students apply what they have learned, regardless of their dominant learning style. The quantity and variety of exercises allow for group work, reflection and application, and writing practice as well as traditional homework exercises. The exercises also engage readers in active learning, integrate writing as part of the critical thinking process, and emphasize skill transference. Aplia", an online homework solution that increases student effort and engagement, is available as an option with this text to provide additional critical thinking practice with automatic grading and immediate feedback that reinforces the skills students are building in class"--Publisher's website.